Enhancing pre-service teachers in learning management competency by TPACK framework study and professional requirement - Prasart Nuangchalerm; Piyaphat Nithitakkharanon (Institute of Advanced Engineering and Science, 2022)
Increasing attention has been placed in recent years to the improvement of learning management competency of pre-service teachers, yet many institutions where the teacher education programs offered have not been provided the effective guidelines. The purposes of this study were to examine the ability of the teaching practice and to propose the enhancement approach on learning management competency of pre-service teacher based on technological pedagogical content knowledge (TPACK) framework. Sample of the study included 385 pre-service teachers studying the fifth-year program at Faculty of Education, Ubon Ratchathani Rajabhat University, Thailand. A learning management competency questionnaire and semi-structured interview were administered to inquire the ability on learning management competency of pre-service teachers during the teaching practice at school. Statistics used for data analysis included frequency distribution, average, standard deviation, and content analysis. Results indicated that pre-service teachers expressed their teaching practices considered each aspect of teaching quality, results ranged from the highest to lowest level were the ability on learner-centered management ( =3.00, S.D.=0.77), the knowledge on teaching design ( =2.96, S.D.=0.72), the assessment and evaluation methods ( =2.95, S.D.=0.74), and the integration of technology ( =2.70, S.D.=0.78), respectively. Recommendations and suggestions were further discussed regarding the enhancement approaches proposed on improving learning management competency of pre-service teachers.